Muscular syndrome manifestations at the patients in the late postoperative period after the herniation of invertebral disk surgical treatment - S. A. Fedyanin (Бюллетень сибирской медицины)
Checkup of 215 patients in the late period after the dick herniation surgical treatment. Middle age (45,6 ± 0,6) years. Postoperative period is (7,4 ± 0,4) years. The patients were examined: neurological status, lumbar spine radiography, magnetic resonance imaging procedure, spinal canal ultrasound investigation, muscular syndrome index determination. Revealed pain syndrome caused by the disk herniation relapse in operated and adjacent segments, spondylosis and spondylarthrosis, spinal canal stenosis, aseptic epiduritis. The pain syndrome at those patients entails by development of the muscular syndrome and pathologic motor skill.